Differences in the Percentage of Fusarium Wilt Disease Attacks and High Vegetative Growth of Purple Eggplant (Solanum melongena L.) Plants with Various Concentrations of Antagonist Fungus Trichoderma harzianum - Ketut Srie Marhaeni Julyasih; I Putu Parwata; Ni Putu Dian Pertiwi (Jurnal Penelitian Pendidikan IPA, 2025)
Microorganisms that have antagonistic properties against pathogens are an alternative as a material for control, such as Trichoderma sp. The use of biological agents has the potential to control plant diseases safely and environmentally friendly, Trichoderma sp is a fungus that can be a biocontrol agent because it is antagonistic to other fungi. Trichoderma sp is a fungus whose habitat is in the soil, including the Ascomycetes class which has green spores. This fungus has the potential for degradation of various heterogeneous substrates in the soil, positive interactions with the host, producing enzymes to improve plant nutrition. Until now, there has not been much research conducted on the competence of Trichoderma sp. isolates in inhibiting the development of Fusarium wilt disease. The purpose of this study was to test the difference in the percentage of Fusarium wilt disease attacks on eggplant plants and plant vegetative growth due to the provision of variations in the concentration of Trichoderma sp. The type of research conducted was a true experimental, with the research design used was a Completely Randomized Design using 6 treatments, namely with the treatment of Trichoderma sp. isolate concentration. grown on rice media with concentrations of 0%, 10%, 20%, 30% 40%, and 50%, each treatment was repeated 5 times so that there were 30 experimental units. The variables observed in this study were the differences in the percentage of Fusarium Wilt disease attacks and the high vegetative growth of purple eggplant plants. The data obtained were analyzed using the analysis of variance of the ANOVA test with a level of 5%. If there is a significant difference, it is continued with the Duncan test at a level of 5%. The results showed that there was a significant difference in the variation of T. harzianum concentration on the percentage of Fusarium wilt disease attacks, and the high growth of purple eggplant plants.